Multiple Approaches to Investigate the Transport and Activity-Dependent Release of BDNF and Their Application in Neurogenetic Disorders. (6th June 2012) - Hartmann, David; Drummond, Jana; Handberg, Erik; Ewell, Sharday; Pozzo-Miller, Lucas
Abstract : Studies utilizing genetic and pharmacological manipulations in rodent models and neuronal cultures have revealed myriad roles of brain-derived neurotrophic factor (BDNF). Currently, this knowledge of BDNF function is being translated into improvement strategies for several debilitating neurological disorders in which BDNF abnormalities play a prominent role. Common among the BDNF-related disorders are irregular trafficking and release of mature BDNF (mBDNF) and/or its prodomain predecessor, proBDNF. Thus, investigating the conditions required for proper trafficking and release of BDNF is an essential step toward understanding and potentially improving these neurological disorders. This paper will provide examples of disorders related to BDNF release and serve as a review of the techniques being used to study the trafficking and release of BDNF.